2003
DOI: 10.1021/cc020091r
|View full text |Cite
|
Sign up to set email alerts
|

Solid Phase Library Synthesis of Cyclic Depsipeptides:  Aurilide and Aurilide Analogues

Abstract: A solid-phase combinatorial synthesis approach toward the cyclic depsipeptide aurilide (1) and related analogues is described. The peptide moiety 2 was assembled on trityl linker-functionalized SynPhase Crowns using an Fmoc strategy. Optimization of the tetrapeptide assembly 5 was carried out using parallel multiple synthesis and LC/MS analysis. The aliphatic moiety 3a was coupled with the solid-supported 2 using DIC/HOBt. Following deprotection and cleavage of linear precursor 26, macrocyclization was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In addition, aurilide B showed net tumor cell killing activity in the hollow fiber assay. There are currently two reports on the synthesis of aurilide analogues for SAR studies (Takahashi et al, 2003;Suenaga et al 2008). A structurally related compound, palau'amide (81) (Fig.…”
Section: Aurilides and Analoguesmentioning
confidence: 99%
“…In addition, aurilide B showed net tumor cell killing activity in the hollow fiber assay. There are currently two reports on the synthesis of aurilide analogues for SAR studies (Takahashi et al, 2003;Suenaga et al 2008). A structurally related compound, palau'amide (81) (Fig.…”
Section: Aurilides and Analoguesmentioning
confidence: 99%
“…Aurilide showed unusually high in vivo antitumor activity in the NCI's hollow-fiber assays, and is expected to be a promising candidate for cancer treatment. Solid-phase library synthesis of aurilide and its derivatives was reported in 2003 [144]. Further structure-cytotoxicity relationship studies revealed that 6-epi-aurilide was almost non-cytotoxic (IC 50 > 4 µg/mL against HeLa S3 cells) [145].…”
Section: Peptides and Depsipeptidesmentioning
confidence: 99%
“…Furthermore, the anti-proliferative effect of this molecule is suggested to operate via the mitochondrial mediated apoptosis based on studies using HCT8 and MCF7 cell lines. There is currently growing interest in developing aurilide-class of molecules as potential anticancer agents as indicated by several reports on its total syntheses and SAR studies [58][59][60][61].…”
Section: Aurilides/lagunamidesmentioning
confidence: 99%